Probabilistic coupled modelling of flash floods events in rural-urban fringe areas : sediment production and deposition processes at the catchment scale - Barros Vanegas, Jaime Marcelo (2017)
Flash flood and sediment deposition events are natural or anthropic caused hazards that produce severe human and economic losses. 1D and 2D Saint-Venant simplifications and several empirical relations are often employ to conduct hazard or probabilistic assessment of these events, despite of several inherent limitations. This work proposes to employ the complete form of the shallow water equations, developing a coupled hydrologic-hydrodynamic model for flash floods, and a coupled splash erosion-morphological model to asses sediment deposition in urbanrural fringe areas, in a probabilistic framework. Results show that rainfall induced contribution to flash flood and sediment deposition estimates may be significant. Furthermore, the proposed methodological procedure could be used in probabilistic risk assessment context, taking into account several physical aspects omitted in traditional approaches.